CMOS 45 GHz vector modulator with gain/phase correction through calibration. Issue 4 (1st February 2013) - Juntunen, E.; Dawn, D.; Laskar, J.; Papapolymerou, J.
Abstract : A 45 GHz vector modulator designed in 45 nm SOI CMOS is presented along with an open‐loop calibration technique for gain/phase correction. The continuous 360° vector modulator consists of a passive quadrature signal generation network followed by a Gilbert cell modulator. The simple, open‐loop calibration procedure results in RMS gain and phase errors less than 0.5 dB and 5°, respectively. The circuit consumes 18 mW of DC power from a 1 V supply.